2003
DOI: 10.1901/jeab.2003.80-159
|View full text |Cite
|
Sign up to set email alerts
|

Bouts of Responding From Variable‐interval Reinforcement of Lever Pressing by Rats

Abstract: Four rats obtained food pellets by lever pressing. A variable-interval reinforcement schedule assigned reinforcers on average every 2 min during one block of 20 sessions and on average every 8 min during another block. Also, at each variable-interval duration, a block of sessions was conducted with a schedule that imposed a variable-ratio 4 response requirement after each variable interval (i.e., a tandem variable-time variable-ratio 4 schedule). The total rate of lever pressing increased as a function of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
73
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 27 publications
11
73
0
Order By: Relevance
“…Our conclusion seems similar to recent findings from Shull and colleagues (Shull, Gaynor, & Grimes, 2001;Shull & Grimes, 2003;Shull, Grimes, & Bennett, 2004). They reported that responses (or IRTs) under single reinforcement schedules can be classified into bouts of responses or pauses, and molar reinforcement rate mainly affects the start of a bout (bout initiation rate), whereas molecular IRT reinforcement affects only the speed of responding within a bout (within-bout response rate).…”
Section: Relation To the Single-schedule Situationsupporting
confidence: 92%
“…Our conclusion seems similar to recent findings from Shull and colleagues (Shull, Gaynor, & Grimes, 2001;Shull & Grimes, 2003;Shull, Grimes, & Bennett, 2004). They reported that responses (or IRTs) under single reinforcement schedules can be classified into bouts of responses or pauses, and molar reinforcement rate mainly affects the start of a bout (bout initiation rate), whereas molecular IRT reinforcement affects only the speed of responding within a bout (within-bout response rate).…”
Section: Relation To the Single-schedule Situationsupporting
confidence: 92%
“…As was discussed in Tanno et al (2010), if we accept Herrnstein's (1970) notion that single schedules can be viewed as a choice situation between experimentally reinforced behavior and endogenously reinforced behavior, our conclusion is consistent with findings from Shull and colleagues (Shull, 2011;Shull, Gaynor, & Grimes, 2001;Shull & Grimes, 2003;Shull, Grimes, & Bennett, 2004) in single-schedule situations. They reported that responses (or IRTs) under single reinforcement schedules can be classified into bouts of responses or pauses, and that reinforcement frequency mainly affects the start of a bout (bout-initiation rate), whereas types of reinforcement schedule (VI and tandem VI-FR or tandem VI-VR) mainly affect the speed of responding within a bout (withinbout response rate).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, it was hypothesized that the previously observed differences in resistance to change of responding maintained by immediate and delayed reinforcement (Bell, 1999;Grace et al, 1998) may have been due to the differential effects of conditions of disruption on underlying response structure. Examining underlying response structure using log survivor plots and a double-exponential model (Shull & Grimes, 2003) failed because responding was not consistently composed of two separate modes (see Figure 3). Even when responding did appear to occur in bouts (e.g., for Pigeon 217), the log survivor functions did not conform to simple double exponential functions that previously have been observed with rats lever pressing and nose poking for food (e.g., Shull & Grimes, 2003;Shull et al, 2001Shull et al, , 2002Shull et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Responding maintained by VI schedules has been shown to occur in two modes-bout initiations (i.e., visits) and within-bout responding (i.e., response engagement; Baum, 2002;Baum & Rachlin, 1969;Blough, 1963;Davison, 2004;Mellgren & Elsmore, 1991;Nevin & Baum, 1980;Pear & Rector, 1979;Shull, Gaynor, & Grimes, 2001). In rats nose poking and lever pressing for food, differences in reinforcement rates have been shown to affect bout-initiation rates, whereas adding a small ratio response requirement to the end of a VI schedule increases within-bout responding (Shull, Gaynor, & Grimes, 2001Shull & Grimes, 2003). Conditions of disruption have been shown to decrease boutinitiation rates relative to baseline, whereas within-bout responding tends to be less affected (Shull, 2004;Shull et al, 2002).…”
Section: ____________________________________________________________mentioning
confidence: 99%